DETERMINAN LOYALITAS KERJA PADA PT BANK ACEH SYARIAH - Budi, M. Arief Setia; Wiratama, Muhammad Jaka (Fakultas Ekonomi, 2024)
This research aims to analyze the influence of religiosity and work placement on work loyalty. This research was conducted on 150 employees with the sample determined using census techniques. Data was collected by collecting Google forms and analyzed using SPSS through multiple linear regression. The results prove that religiosity and work placement have a partial and simultaneous effect on work loyalty. The higher the religiosity of the employees in this study, the higher their work loyalty. Likewise, the more precise the job placement determined by the company, the higher the work loyalty towards PT Bank Aceh Syariah Operational Head Office.Keywords: Religiosity, Job Placement, Work Loyalty